EFEKTIVITAS PERENDAMAN DAGING SAPI DALAM EKSTRAK PEGAGAN (Centelia asiatica L.) - Yunardi Irdha; Mirdhayati dan; Endah Purnamasari (Jurnal Peternakan, 2007)
Meat preservation generally carries put by refrigeration, heating and adding chemical preservation materials. Purpose of the· preservation is to keep meat quality, because meat is one of high nutrient food materials. The content of nutrient in meat is good media for the growth of bacteria, and then they can decrease meat quality. Hence; it needs some treatments, one of them is a natural preservation such as extract of Centella asiatica L. that content salt minerals and bacterial compound, and it can block and remove bacteria.The purpose of this research is to determine influence extract of Centella asiatica 1. with different concentrations to water content, pH, and total bacterial colony, and sensorial value (color, texture, and aroma) of beef. This research uses a Complete Random Design that consists of four treatments with three repeat. The treatments are adding extract of Centella asiatica L. for 0 ml, 10 ml, 20 ml, 30 m1. Submersion of beef within the extract of Centella asiatica L. takes about 30 minutes. Resulted variables data statically processed by using various analysis. If the differences happen among the treatments, then must be perform following test by using Duncan Multiple Range Test (DMRT). Theresult of this research show that the beef submersions with adding 30 ml of extract of Centella asiatica L. is most effective in decreasing water content of beef to 61.32%, pH to 5.17, total bacterial colony to 5:1 x 105 CFU / gram and color change to undesirable brownish red. But it's not influential to texture and aroma. Beef have in a row pattern, approximately soft and nice look, fresh blood aroma.